The Religious Meaning of Language in Judaic Culture - Shira Wolosky (St Andrews Encyclopaedia of Theology)
Judaic cultures have a commitment to language that is exceptional. Language practices – the reading and writing of scrolls and books, their interpretation as commentaries on commentaries, engaged with the letter both of text and as act – is central to Judaic conduct, thought, study, worship, and spirituality. This positive status and decisive focus on language extends through Judaic praxis, interpretive methods, commentary, and philosophy. It is basic to Rabbinic as well as Jewish mystical trends, where language is embraced as the core means of relationship between the divine and the human, enacted both in study and its concrete performance. In a way pivotal to Judaic cultures, it is through linguistic engagement that humans are seen not only to understand but to participate in the emergence of religious meaning. This article traces the sacrality of language through a series of hermeneutic and philosophical topics, from Talmudic and Midrashic engagements, to Maimonides, and into modern philosophy of Emmanuel Levinas, Jacques Derrida, and Gershom Scholem.